Variables Impacting Mutual Fund Expense Ratio: The Indian Midcap Mutual Fund Experience - MANDA, VIJAYA KITTU; RANI, DR.P SAI; POLISETTY, DR. ARUNA (The journal of contemporary issues in business and government, 2021)
With an increase in the number of fund houses entering the asset management business, the Indian Mutual Fund Industry has turned into a competitive marketplace. An increase in the number of schemes translates to increased choice (and confusion) for investors, while for fund managers, it means more pressure to beat the benchmark indices. Correlation research method is used on scheme variables such as Assets Under Management (AUM), Expense Ratio, and the Monthly Returns of select Indian Midcap Schemes for the period January 2016 to 2021 to determine the statistical relationships between the variables. Three schemes from amongst the midcap schemes, after putting them into clusters, are picked for this study. Findings from this research can help fund managers, and Asset Management Companies (AMCs) better manage their schemes by tweaking expenses and further maximizing investor returns.